ChemInform Abstract: Self‐Assembled Metal‐Organic Polyhedra: An Overview of Various Applications. Issue 18 (April 2016) - Vardhan, Harsh; Yusubov, Mekhman; Verpoort, Francis
Abstract: Review: 217 refs.